Nonspecific resistance training and swimming performance: strength or power? A systematic review - Muniz-Pardos, B.; Gomez-Bruton, A.; Matute-Llorente, A.; Gonzalez-Aguero, A.; Gomez-Cabello, A.; Gonzalo-Skok, O.; Casajus, J. A.; Vicente-Rodriguez, G (The Journal of Strength and Conditioning Research, 2022)
The purpose of this systematic review was to determine the type of nonspecific resistance intervention that is more effective to enhance swimming performance and to determine the nonspecific strength- or power-related variable that better predicts swimming performance. A search was conducted on PubMed, Cochrane Plus, and SportDiscus up to June 2018. Studies were distributed into 4 categories: dry-land strength (DLS), dry-land power (DLP), combination of training methods, and strength and power in start performance. From 1,844 citations, 33 met the inclusion criteria. Cross-sectional DLS studies showed positive associations between swimming performance and DLS development (especially through upper-body isometric assessments), although the efficacy of DLS training interventions remains unclear. Dry-land power training (principally through plyometrics) was a proficient, nonspecific method to enhance swimming block start performance (SBS; the start phase off the block and during the first 5-15 m), and jump assessment was the best predictor of SBS. Some pioneering nonspecific practices such as the acute exposure to high altitude or the maintenance of a high core temperature during the transition phase before competition seem to improve performance, although more research is required to confirm their efficacy. Further high-quality intervention studies are required to clarify the effect of DLP training on sprint swimming performance.